Virtual Reality Facilitates Engagement in Physical Therapy in the Pediatric CVICU. Issue 1 (January 2021) - Hemphill, Sydney; Nguyen, Alan; Kwong, Joann; Rodriguez, Samuel T.; Wang, Ellen; Caruso, Thomas J.
Abstract : Purpose: The purpose of this report is to demonstrate the successful application of virtual reality to improve physical therapy in the pediatric cardiovascular intensive care unit. Early mobilization and cognitive stimulation improve morbidity of critically ill children. However, maintaining child engagement with these therapies can be challenging, especially during extended intensive care stays. Summary of Key Points: While virtual reality has been successfully used as an analgesic and anxiolytic in the cardiovascular intensive care unit, this report demonstrates its novel use as a tool to augment physical therapy for a child who had been debilitated after heart transplantation. Virtual reality encouraged the child to engage in physical therapy sessions, participate for greater durations, and directly address barriers to discharge. Conclusions and Recommendations for Clinical Practice: While further studies are needed to define best practice, this report demonstrates that virtual reality can be safely used for carefully selected and monitored children in critical care. Abstract : The purpose of this report is to demonstrate the successful application of virtual reality to improve physical therapy in the pediatric cardiovascular intensive care unit.